A novel IGSF1 mutation in a large Irish kindred highlights the need for familial screening in the IGSF1 deficiency syndrome. (1st October 2018) - Roche, Edna F.; McGowan, Anne; Koulouri, Olympia; Turgeon, Marc‐Olivier; Nicholas, Adeline K.; Heffernan, Emmeline; El‐Khairi, Ranna; Abid, Noina; Lyons, Greta; Halsall, David; Bonomi, Marco; Persani, Luca; et al.
Summary: Objective: Loss‐of‐function mutations in IGSF1 result in X‐linked central congenital hypothyroidism (CeCH), occurring in isolation or associated with additional pituitary hormone deficits. Intrafamilial penetrance is highly variable and a minority of heterozygous females are also affected. We identified and characterized a novel IGSF1 mutation and investigated its associated phenotypes in a large Irish kindred. Design, Patients and Measurements: A novel hemizygous IGSF1 mutation was identified by direct sequencing in two brothers with CeCH, and its functional consequences were characterized in vitro. Genotype‐phenotype correlations were investigated in the wider kindred. Results: The mutant IGSF1 protein (c.2318T > C, p.L773P) exhibited decreased plasma membrane expression in vitro due to impaired trafficking from the endoplasmic reticulum. Ten hemizygous males and 11 heterozygous females exhibited characteristic endocrine deficits. Ireland operates a TSH‐based CH screening programme, which does not detect CeCH; therefore, genetic ascertainment preceded biochemical diagnosis of moderate CH in five of seven boys as well as their 75‐year‐old grandfather. Clinical features potentially attributable to hypothyroidism were variable; normal free T3 (FT3) and low/low normal reverse T3 (rT3) concentrations suggested that preferential deiodination of FT4 to FT3 may help maintain tissue euthyroidism in some individuals. However, neonatal jaundice, delayed speech or growth, and obesity were observed in seven subjects in whom diagnosis was delayed. Conclusions: As observed with other IGSF1 mutations, p.L773P results in variably penetrant IGSF1 deficiency syndrome. Our observations emphasize the need for multi‐generation genetic ascertainment in affected families, especially where TSH‐based CH screening programmes may fail to detect CeCH at birth.